Analisis Pengelolaan Administrasi Keuangan Dan Anggaran Pada Kantor Camat Waigete - Matilda Arnista Ja’o; Andreas Rengga; Elisabet Luju (Universitas Nusa Nipa Maumere, 2023)
This study aimed to determine the financial and budget administration management at Waigete Sub-District Office, Sikka Regency. This study was a descriptive qualitative and employed a case study design. The technique of analysis employed in this research was descriptive analysis consisting of collecting and filtering information thoroughly and in detail, then it was elaborated to obtain a clear description. Data was collected using observation, documentation, and interviews. Based on the results of the study, it was concluded that the management of financial and budget administration at the Waigete sub-district office starting from planning, budgeting, implementation, and administration were good while the issues were in reporting and accountability for budget implementation. They were not optimal due to the lack of human resources quality (HR) who had accrual-based abilities or skills in utilizing existing information technology and delays or time mismatches in annual financial reporting. The delay in question was regarding the delay in the completeness of official travel report receipts used as transaction evidence to make accountability letters. Thus, the quantity of acceleration of programs and the submission of accountability reports was not optimal.